Associations between nucleosome phasing, sequence asymmetry, and tissue-specific expression in a set of inbred Medaka species. (December 2015) - Nakatani, Yoichiro; Mello, Cecilia; Hashimoto, Shin-ichi; Shimada, Atsuko; Nakamura, Ryohei; Tsukahara, Tatsuya; Qu, Wei; Yoshimura, Jun; Suzuki, Yutaka; Sugano, Sumio; Takeda, Hiroyuki; Fire, Andrew; et al.
Abstract Background Transcription start sites (TSSs) with pronounced and phased nucleosome arrays downstream and nucleosome-depleted regions upstream of TSSs are observed in various species. Results We have characterized sequence variation and expression properties of this set of TSSs (which we call "Nucleocyclic TSSs") using germline and somatic cells of three medaka (Oryzias latipes ) inbred isolates from different locations. We found nucleocyclic TSSs in medaka to be associated with higher gene expression and characterized by a clear boundary in sequence composition with potentially-nucleosome-destabilizing A/T-enrichment upstream (p < 10−60 ) and nucleosome- accommodating C/G-enrichment downstream (p < 10−40 ) that was highly conserved from an ancestor. A substantial genetic distance between the strains facilitated the in-depth analysis of patterns of fixed mutations, revealing a localization-specific equilibrium between the rates of distinct mutation categories that would serve to maintain the conserved sequence anisotropy around TSSs. Downstream of nucleocyclic TSSs, C to T, T to C, and other mutation rates on the sense strand increased around first nucleosome dyads and decreased around first linkers, which contrasted with genomewide mutational patterns around nucleosomes (p < 5 %). C to T rates are higher than G to A rates around nucleosome associated with germline nucleocyclic TSS sites (p < 5 %), potentially due to the asymmetric effect of transcription-coupled repair. Conclusions Our results demonstrate an atypical evolutionary process surrounding nucleocyclic TSSs.